Conflict Management Strategies for Institutional Character in Pesantren - Maghvirani, Rohila Chindy; Ulfah, Maziah; Ningrum, Annisa Mukti; Solichatun, Yulia; Rahayu, Iin Tri; Mahpur, Mohamad (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
In any organization or institution that involves many individuals, differences in thinking are commonplace. However, often these differences can lead to misunderstandings, incompatibilities, and even conflicts within the organization, including within the organizational body. Boarding schools are no exception. Therefore, good conflict management is needed in an institution. Conflict management is basically able to be one of the reasons for the creation of characteristics that are so inherent in the scope of the institution. This study aims to explore 1) the forms of conflict that occur in the Tsurayya Islamic Boarding School (TISMA) Educational Institution, 2) conflict management strategies used to shape institutional character in the TISMA environment. The research method used is qualitative, using a case study approach. The respondents of this study were 3 resource persons, including (E) as the head of boarding school, (G) as a class teacher and (N) as a class teacher. The data analysis technique used is the coding stage technique. The results showed that there were conflicts that occurred among the scope of educators. The conflict is in the form of personal friction and system conflict as if there are fellow teachers who demand professionals but they cannot be professional. Then there are conflicts that occur with students in the form of juvenile delinquency such as sleeping during lessons, fighting and bullying. In resolving these conflicts, the Tsurayya Islamic Boarding School institution prioritizes deliberation or discussion, self-disclosure, leadership advice, personal approaches, and so on. Conflict management carried out at the Tsurayya Islamic Boarding School institution also seeks to resolve conflicts with Islamic values as stated in the institution's vision and mission. Thus, in this case creating an institutional character in the form of; discussion / deliberation, Tabayyun, and professionalism.